2008
DOI: 10.1002/anie.200801479
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Catalytic CO Oxidation Activity of Nanoparticles

Abstract: Although extended gold surfaces are generally considered chemically inert [1,2] nanosized (< 5 nm) gold particles can be very effective catalysts for a number of oxidation reactions. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] There are reports of similar size effects for silver catalysts. [18,19] The origin of the nanoeffects in the catalytic properties of these metals is widely debated, [15] and no consensus has been reached. Based on a set of density functional theory calculations of the full reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
442
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 413 publications
(465 citation statements)
references
References 36 publications
20
442
3
Order By: Relevance
“…It has been found that undercoordinated Au atoms have increased chemical activity. 58,59 Of course, turnover for particular reactions will also depend on lateral interactions between adsorbates and thiolate species. In the case of very strong repulsive interactions, thiolate adsorption on Au might even result in decrease of Au reactivity.…”
Section: Thiolate-covered Gold Nanoparticlesmentioning
confidence: 99%
“…It has been found that undercoordinated Au atoms have increased chemical activity. 58,59 Of course, turnover for particular reactions will also depend on lateral interactions between adsorbates and thiolate species. In the case of very strong repulsive interactions, thiolate adsorption on Au might even result in decrease of Au reactivity.…”
Section: Thiolate-covered Gold Nanoparticlesmentioning
confidence: 99%
“…5 Their enhanced catalytic properties for CO oxidation are often attributed, much like in nanoparticle catalysts, to the presence of undercoordinated Au atoms. [6][7][8] Among other factors that have been recently discussed in terms of their potential influence on the catalytic activity of NPG are: surface to volume ratio, mechanical strain, as well as the role of residual Ag. 5 Among these factors, the strain effect on reactivity in nanoscale metal catalysts is a topic of intense experimental and theoretical research.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it becomes easy to establish trends for reactions allowing a first screening for new catalytic materials by means of few simple descriptors. 6,20,21,22,23 …”
mentioning
confidence: 99%